A Research-Based Study of Social Media and Digital Culture in the Light of Islamic Ethical Principles: Social and Civilizational Challenges of the Modern Age - Hafiza Areeba Khan; Iffat Majeed; Muhammad Mehtab (Journal of Religion and Society, 2026)
This research article presents a critical and analytical study of social media and digital culture in the light of Islamic ethical principles, focusing on the contemporary social and civilizational challenges of the modern age.The study explores the necessity and importance of social media, examines its conceptual relevance in relation to the Islamic notion of Madinah as a morally structured society, and incorporates perspectives of modern scholars and media experts regarding its role and impact.The article emphasizes that,from an Islamic viewpoint, the use of social media is not merely a matter of freedom of expression but a moral responsibility and a trust. Core Islamic values such as amr bil Ma‘ruf and nahi ‘anil munkar, avoidance of sharing unverified information, refraining from mockery, falsehood, abusive language, and character assassination are highlighted as essential ethical guidelines for digital engagement. Furthermore, the study underscores the obligation to distinguish between good and evil, promote positive content, ensure responsible dissemination of information, and contribute to social reform through both individual and collective efforts, including the role of legal and regulatory institutions. The article also critically examines the major social and moral challenges arising from contemporary digital culture, such as waste of time, social isolation, negligence in religious obligations, spread of unauthentic and immoral content, deterioration of family life and relationships, physical and psychological harm, political and religious hatred, abusive discourse, false accusations, and the adverse effects of social media on children and adolescents.The study concludes that if social media is utilized within the framework of Islamic ethical principles, it can serve as a powerful tool for moral development, social harmony, and constructive civilizational growth,offering meaningful solutions to the challenges posed by the modern digital age. Keywords: Social media, Digital Culture, Islamic Moral Framework, Media Ethics, Amr bil Ma‘ruf wa Nahi ‘anil Munkar, Ethical Communication, InformationResponsibility, Social and Moral Reform, Contemporary Societal Challenges, Digital Civilization